Investigation on Harmonic Tuning for Active Ku-Band Rectangular Dielectric Resonator Antennas - Anda Guraliuc; Giuliano Manara; Paolo Nepa; Giuseppe Pelosi; Stefano Selleri (International Journal of Antennas and Propagation)
A slot-coupled rectangular dielectric resonator antenna (DRA) operating in the 14–14.5 GHz frequency band is investigated as a possible radiating element for an active integrated antenna of a transmitting phased array. The effectiveness of the resonator shape factor on achieving harmonic tuning is addressed. Simulation results show that the DRA shape factor can be used to provide a fine tuning of the DRA input impedance both at the fundamental frequency and its first harmonics, so synthesizing the proper load for the optimization of the microwave amplifier power-added efficiency (PAE).